2003
DOI: 10.1177/1099800403252603
|View full text |Cite
|
Sign up to set email alerts
|

A Current Review of Ebola Virus: Pathogenesis, Clinical Presentation, and Diagnostic Assessment

Abstract: Ebola hemorrhagic fever (EHF) is an acute viral syndrome that presents with fever and an ensuing bleeding diathesis that is marked by high mortality in Medicine, Room 52-175, Center for Health Sciences, Los Angeles, CA 90095; phone: 310-825-1153; e-mail: acasillas@mednet.ucla.edu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 21 publications
(32 reference statements)
1
59
0
Order By: Relevance
“…The coagulation mechanism inside the blood vessels is also activated to cause intravascular coagulation. Death can occur either due to coagulation or due to severe blood loss [16]. Thrombocytopenia, consumption of clotting factors, and increased concentrations of fibrin degradation products are major mechanisms responsible for coagulopathy during EBOV infections.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The coagulation mechanism inside the blood vessels is also activated to cause intravascular coagulation. Death can occur either due to coagulation or due to severe blood loss [16]. Thrombocytopenia, consumption of clotting factors, and increased concentrations of fibrin degradation products are major mechanisms responsible for coagulopathy during EBOV infections.…”
Section: Pathogenesismentioning
confidence: 99%
“…In humans, the rates of genetic changes occurring in EBOV may be 100 times slower than that in influenza A viruses; however, the divergence of EBOV was reported to have taken place several thousand years ago [13,14]. The EBOV envelope glycoprotein (eGP) plays multiple functions in viral pathogenesis as it aids in virus attachment and entry to cells, causes cell rounding, down-regulates host surface proteins, enhances virus assembly and budding, and also mediates widespread inflammation, cytotoxicity, and cellular damage, while secretary glycoprotein (sGP) is secreted by the virus infected host cells [15][16][17].…”
Section: Etiologymentioning
confidence: 99%
“…2,57 Some vaccines under trial have been shown to protect NHPs: a replication-incompetent adenovirus expressing the EBOV glycoprotein (29-31), a replication-competent vesicular stomatitis virus (VSV) expressing GP (7,15), a recombinant 48 paramyxovirus expressing GP (4), and virus-like particles (38,41). 5 In the absence of effective treatment and vaccine, raising awareness regarding the risk factors and personal protective measures is the only way to reduce human infection and death.…”
Section: Preventionmentioning
confidence: 99%
“…41 The virus has the specialized mechanisms to evade the immune system and the course of illness results from a complex pathogenic mechanism. 16 In a study it is shown that fatal outcome is associated with aberrant innate immune responses and suppression of the adaptive immunity.…”
Section: Pathogenesismentioning
confidence: 99%
“…Disease outbreaks with these viruses have significant medical and social impacts. Case fatality rates can be as high as 65% for Lassa virus (LASV) and as high as 90% for ebolaviruses (3,4). Their high mortality rates combined with their ease of transmission and the lack of vaccines or effective treatments render them extremely dangerous pathogens.…”
mentioning
confidence: 99%